2010
DOI: 10.3109/09513590.2010.487591
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between endometrial thickness and pregnancy rates in GnRH antagonist down-regulated ICSI cycles

Abstract: For achieving pregnancy, endometrial thickness on the day of hCG is not a determining parameter, and the only significant determinent is AFC in GnRH antagonist down-regulated ICSI cycles.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 20 publications
1
17
0
Order By: Relevance
“…The majority of previous studies concur that appropriate thickness of the endometrium is essential for embryo implantation. It has been observed that clinical pregnancy rates increase once the endometrial thickness increases to >14 mm on the day of hCG application, whereas implantation and pregnancy rates were almost zero when endometrial thickness was <6-7 mm (21,(23)(24)(25)(26). In the present study, the endometrium of the ultra-long protocol group was thicker on the day of hCG administration, as compared with that of the long protocol group, and the endometrial morphologies on day of ET were type C in both protocols.…”
Section: Discussionmentioning
confidence: 98%
“…The majority of previous studies concur that appropriate thickness of the endometrium is essential for embryo implantation. It has been observed that clinical pregnancy rates increase once the endometrial thickness increases to >14 mm on the day of hCG application, whereas implantation and pregnancy rates were almost zero when endometrial thickness was <6-7 mm (21,(23)(24)(25)(26). In the present study, the endometrium of the ultra-long protocol group was thicker on the day of hCG administration, as compared with that of the long protocol group, and the endometrial morphologies on day of ET were type C in both protocols.…”
Section: Discussionmentioning
confidence: 98%
“…Of the 2874 potentially relevant studies screened by electronic databases, 2830 were excluded owing to irrelevant and duplicate topics. The full-text articles for the remaining 44 studies were evaluated, and 30 studies met the inclusion criteria and were included in this study (Rinaldi et al, 1996;Weissman et al, 1999;De Geyter et al, 2000;Basir et al, 2002;Dietterich et al, 2002;Yoeli et al, 2004;Aboulghar et al, 2005;Rashidi et al, 2005;Zhang et al, 2005;Amir et al, 2007;Richter et al, 2007;McWilliams and Frattarelli, 2007;Al-Ghamdi et al, 2008;Dechaud et al, 2008;Bozdag et al, 2009;Okohue et al, 2009;Traub et al, 2009;Chen et al, 2010;Kinay et al, 2010;Kuc et al, 2011;Singh et al, 2011;Zhao et al, 2012;Wu, 2014;Bu and Sun, 2015;Fang et al, 2016;Yuan et al, 2016;Liu et al, 2018;Ribeiro et al, 2018;Wang et al, 2018;Yang et al, 2018). No new eligible studies were found after a manual search of the reference lists.…”
Section: Literature Search and Study Characteristicsmentioning
confidence: 99%
“…For example, several studies showed that the antiestrogenic effect of CC on the endometrium might be overcome by the adjunctive use of exogenous estrogens, [15][16][17][18] while other studies showed that the addition of some types of exogenous estrogens did not significantly enhance the endometrial thickness. 19,20 These different outcomes could be the result of several factors, such as the type, dosage, and route of administration of the exogenous estrogens used for the treatment. 16,18,19 Estradiol valerate (EV) is an oral synthetic form of estradiol.…”
Section: Introductionmentioning
confidence: 99%